Strengthening The Use Of Language As A Communication Tool In Improving Teacher Performance In Indonesian Schools, Kuala Lumpur, Malaysia - Anwar, Saiful; Utaminingsih, Sri; Napasti, Friny; Prasetyawan, Enggar; Sesriyani, Lodya (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
This PkM is an implementation of research previously conducted by the PkM team entitled Factors that influence teacher performance. There are many factors that can be used to improve teacher performance, one important factor is a teacher's communication skills. The communication in question is the communication process carried out by teachers and students in the classroom. Teachers are not only required to communicate well, but also use correct grammar so that there are no multiple interpretations by students. These communication skills are included in eight teacher teaching skills, namely skills to open lessons, skills to close lessons, explanation skills, skills to provide variations, skills to provide reinforcement, skills to manage the class, skills to guide small group discussions, skills to manage the class and skills to teach small groups and problems. Communication skills are very necessary, especially for schools that use multilingual teaching and learning activities. One of the schools that uses multilingual school instruction is the Sekolah Indonesia Malaysia Kuala Lumpur. This school uses three languages ​​of instruction, namely Malay, Indonesian and English. This community service is needed to provide a new perspective to teachers at Indonesian schools in Kuala Lumpur that the use of language should be as simple as possible but the learning objectives that have been set can be achieved. Keywords: Communication, Basic Teaching Skills, Teacher